Network Pharmacology-Based Approach to Revealing Biological Mechanisms of Qingkailing Injection against IschemicStroke: Focusing on Blood-Brain Barrier. (27th August 2020) - Zhang, Shuang; Wang, Xueqian; Cheng, Fafeng; Ma, Chongyang; Fan, Shuning; Xu, Wenxiu; Jin, Na; Liu, Shuling; Lv, Kai; Wang, Qingguo
Abstract : Ischemic stroke is the most common type of cerebrovascular accident worldwide. It causes long-term disability and death. Qingkailing (QKL) injection is a traditional Chinese patent medicine which has been clinically applied in the treatment of ischemic stroke for nearly thirty years. In the present study, network pharmacology combined with experimentation was used to elucidate the mechanisms of QKL. ADME screening and target prediction identified 62 active compounds and 275 targets for QKL. Topological screening of the protein-protein interaction (PPI) network was used to build a core PPI network consisting of 408 nodes and 17, 830 edges. KEGG enrichment indicated that the main signaling pathway implicated in ischemic stroke involved hypoxia-inducible factor-1 (HIF-1). Experimentation showed that QKL alleviated neurological deficits, brain infraction, blood-brain barrier (BBB) leakage, and tight junction degeneration in a mouse ischemic stroke model. Two-photon laser scanning microscopy was used to evaluate BBB permeability and cerebral microvessel structure in living mice. HIF-1 α, matrix metalloproteinase-9 (MMP-9), and tight junction proteins such as occludin, zonula occludins-1 (ZO-1), claudin-5, and VE-Cadherin were measured by western blotting. QKL upregulated ZO-1 and downregulated HIF-1 α and MMP-9. QKL has a multiapproach, multitarget, and synergistic effect against ischemic stroke.